Toward a Better Understanding of Genotype × Environment × Management Interactions—A Global Wheat Initiative Agronomic Research Strategy - Beres, Brian L.; Hatfield, Jerry L.; Kirkegaard, John A.; Eigenbrode, Sanford D.; Pan, William L.; Lollato, Romulo P.; Hunt, James R.; Strydhorst, Sheri; Porker, Kenton; Lyon, Drew; Ransom, Joel; Wiersma, Jochum (Frontiers in Plant Science, 2020)
The Wheat Initiative (WI) and the WI Expert Working Group (EWG) for Agronomy (www.wheatinitiative.org) were formed with a collective goal to “coordinate global wheat research efforts to increase wheat production, quality, and sustainability to advance food security and safety under changing climate conditions.” The Agronomy EWG is responsive to the WI’s research need, “A knowledge exchange strategy to ensure uptake of innovations on farm and to update scientists on changing field realities.” The Agronomy EWG aims to consolidate global expertise for agronomy with a focus on wheat production systems. The overarching approach is to develop and adopt a systems-agronomy framework relevant to any wheat production system. It first establishes the scale of current yield gaps, identifies defensible benchmarks, and takes a holistic approach to understand and overcome exploitable yield gaps to complement genetic increases in potential yield. New opportunities to increase productivity will be sought by exploiting future Genotype × Environment × Management synergies in different wheat systems. To identify research gaps and opportunities for collaboration among different wheat producing regions, the EWG compiled a comprehensive database of currently funded wheat agronomy research (n = 782) in countries representing a large proportion of the wheat grown in the world. The yield gap analysis and research database positions the EWG to influence priorities for wheat agronomy research in member countries that would facilitate collaborations, minimize duplication, and maximize the global impact on wheat production systems. This paper outlines a vision for a global WI agronomic research strategy and discusses activities to date. The focus of the WI-EWG is to transform the agronomic research approach in wheat cropping systems, which will be applicable to other crop species.